Theater of the Oppressed and bullying: nursing performance in school adolescent health - Lidiane Cristina da Silva Alencastro; Jorge Luiz da Silva; André Vilela Komatsu; Fabiane Blanco Silva Bernardino; Flávia Carvalho Malta de Mello; Marta Angélica Iossi Silva (Associação Brasileira de Enfermagem, 2020)
ABSTRACT Objective: to assess the effects of an intervention based on the Theater of the Oppressed in reducing school bullying. Method: a quasi-experimental study with 232 first-year high school students from two public schools in the city of Cuiabá, Mato Grosso State, Brazil. An intervention was performed with the Theater of the Oppressed, a theatrical methodology created by Augusto Boal and inspired by Paulo Freire's "Pedagogy of the Oppressed", in which one school composed the intervention group, and another school, the comparison group. Both groups were assessed for involvement in bullying situations before and after intervention. For data analysis, Poisson Regression models with random effect were used. Results: intervention group presented a significant decrease in direct victimization (physical and verbal aggression). Conclusion: the Theater of the Oppressed represents an important strategy in reducing bullying victimization among school adolescents.